تحليل أسئلة الاختبار في تقويم تعليم اللغة العربية (بحث وصفي في الصف الأول المتوسط بمعهد الكوثر سيمالونجون( - Sri Utari, Sri (Cahaya Ilmu Bangsa Institute, 2025)
Each learning activity has an evaluation to review the success of a learning activity. This study focuses on the Arabic subject at the Al-Kautsar Simalungun Modern Islamic Boarding School, which is conducted based on the problem formula in the following research 1) has the item on the evaluation of Arabic learning in the first class of the al-Kautsar Islamic Boarding School been in accordance with its formulated purpose? 2) how is the validity and reliability of the items regarding the evaluation of Arabic learning in the first class of Alkautsar Islamic boarding school? Then the goal in this study is 1) to find out the conformance of the questions with the aim of learning Arabic in the first class of Al-Kautsar Islamic boarding school, 2) to find out the validity and reliability of the items regarding the evaluation of Arabic learning in the first class of Al-Kautsar Islamic boarding school. This study is a qualitative study and uses descriptive methods, methods of collecting data by interview, observation, and documentation, and methods of data analysis using Miles and Huberman methods. The results of this study are 1) that the problem items that have been given to students in the semester exam are almost entirely in accordance with the goals formulated, there are only a few problems that have not been in accordance with the goals of the Arabic language study that have been determined at the Pondok Pesantren Al-Kautsar Simalungun, which has been established in Pondok Pesantren. 2) For the validity and reliability of the Arabic examination questions, it is found that almost all of the questions tested have been valid, i.e. the tests given are appropriate to measure students' abilities after learning Arabic. For the reliability of the problem, the result is that the Arabic language that has been tested is completely reliable.